Serological surveillance of healthcare workers to evaluate natural infection- and vaccine-derived immunity to SARS-CoV-2 during an outbreak in Dili, Timor-Leste. (June 2022) - Arkell, Paul; Gusmao, Celia; Sheridan, Sarah L; Tanesi, Maria Y; Gomes, Nelia; Oakley, Tessa; Wapling, Johanna; Alves, Lucsendar; Kopf, Stacey; Sarmento, Nevio; Barreto, Ismael Da Costa; Amaral, Salvador; et al.
Abstract: Background Serosurveillance can be used to investigate the extent and distribution of immunity to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) within a population. Characterisation of humoral immune responses gives insight into whether immunity is infection- or vaccine-derived. Methods A longitudinal study of health care workers (HCWs) in Dili, Timor-Leste, was conducted during vaccine rollout (ChAdOx1) and a concurrent SARS-CoV-2 outbreak. Results A total of 324 HCWs were included at baseline (April-May 2021). Out of those, 32 (9.9%) were seropositive for anti-nucleocapsid protein (anti-N) IgG antibodies, indicating a significant sub-clinical infection among HCWs early in the local outbreak. Follow-up was conducted in 157 (48.5%) participants (July-September 2021), by which time there had been high uptake of vaccination (91.7%), and 86.0% were seropositive for anti-spike protein antibodies. Acquisition of anti-N antibodies was observed in partially vaccinated HCWs (30/76, 39.5%), indicating some post-dose-1 infections. Discussion Serosurveillance of HCWs may provide early warning of SARS-CoV-2 outbreaks and should be considered in non-endemic settings, particularly where there is limited availability/uptake of testing for acute infection. Characterisation of humoral immune responses may be used to assess vaccine impact and coverage. Such studies should be considered in national and international efforts to investigate and mitigate against future emerging pathogens.